2021
DOI: 10.3390/s21175810
|View full text |Cite
|
Sign up to set email alerts
|

Modular Software Architecture for Local Smart Building Servers

Abstract: This paper presented the architecture and construction of a novel smart building system that could monitor and control buildings’ use in a safe and optimal way. The system operates on a Raspberry local server, which could be connected via the cloud technology to a central platform. The local system includes nine modules that inter-communicate. The system detects sensor faults, and provides a friendly interface to occupants. The paper presented the software architecture IoT used for the building monitoring and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The prototype tests have shown that any registered smartphone with the Android operating system can control domestic electronic devices attached to the proposed IoT platform. On the other hand, some prototypes were implemented based on innovative panels, whereas the electronic components and microcontrollers were joined for testing and demonstration purposes [22]- [29].…”
Section: Related Workmentioning
confidence: 99%
“…The prototype tests have shown that any registered smartphone with the Android operating system can control domestic electronic devices attached to the proposed IoT platform. On the other hand, some prototypes were implemented based on innovative panels, whereas the electronic components and microcontrollers were joined for testing and demonstration purposes [22]- [29].…”
Section: Related Workmentioning
confidence: 99%
“…Fig. 1 Architecture of the comprehensive smart platform for social housing (Lagsaiar et al, 2021) The platform is connected to a BIM model of the social housing complex, which includes a spatial description of the complex and the properties of its components. It provides tools for the 3D visualization of the complex and its components.…”
Section: Communication Channelsmentioning
confidence: 99%
“…The social housing complex is monitored by smart sensors that measure and transmit real-time data to the platform (Lagsaiar et al, 2021). Smart monitoring covers a multitude of parameters, such as indoor comfort, air quality, energy and water consumption, and security parameters, including building access, smoke detection, movement detection, and survey cameras.…”
Section: Data Collectionmentioning
confidence: 99%
“…These modular components execute specific services that can be used in multiple domains. As an example, Lagsaiar et al [72] developed a system by using existing software modules, an approach that was characterized by simplicity, reliability, low cost and ease of construction. Thus, enablers are software components that provide multiple services, developed either for general or specific usage in different domains, that can be used by smart applications [73].…”
Section: Solution Descriptionmentioning
confidence: 99%